2017
DOI: 10.18203/2394-6040.ijcmph20175604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smartphone use on quality of sleep among medical students

Abstract: Background: Smartphone with its various functionalities has become an essential part of our daily activities and its use has been increasing. This has raised concern about its overuse and addiction especially in students. It is known that poor sleep is very common among medical students; there are many studies on sleep quality and its determinants in medical students but very few relating sleep quality and smartphone addiction. The main objective of this study was to investigate the relationship between smartp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
1
27
0
4
Order By: Relevance
“…The negative effects of using smartphones include psychological dimensions (Kuss & Griffiths, 2011). Smartphone addiction upsets the quality of students' sleep (Ibrahim et al, 2018;Kurugodiyavar et al, 2017;Sahin et al, 2013;Wang et al, 2019) and can lead to insomnia (Van Deursen et al, 2015). Several studies have also connected smartphone use with mental illness, including stress and anxiety (Boumosleh & Jaalouk, 2017;Samaha & Hawi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of using smartphones include psychological dimensions (Kuss & Griffiths, 2011). Smartphone addiction upsets the quality of students' sleep (Ibrahim et al, 2018;Kurugodiyavar et al, 2017;Sahin et al, 2013;Wang et al, 2019) and can lead to insomnia (Van Deursen et al, 2015). Several studies have also connected smartphone use with mental illness, including stress and anxiety (Boumosleh & Jaalouk, 2017;Samaha & Hawi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mean SAS score was 102.85, that is compatible with the mean SAS 102.93 found in a cross-sectional study on a sample of 240 undergraduate medical students of KIMS, Hubballi. [ 14 ] A study conducted by Ammati R, Kakunje A, Karkal R, Nafisa D, Kini G, and Chandrashekaran P on students of medical universities in south India revealed that 46% of the students were using mobile phones for 4-6 hours and 14% of students were using 7-9 hours in a day. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The cross-sectional study conducted by Kurugodiyavar M D, Sushma H R, Godbole M, and Nekar M S at undergraduate medical students of KIMS, Hubbali reported the mean PSQI to be 4.80 and 51.25% were good sleepers, whereas 48.75% were poor sleepers. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations